2006
DOI: 10.1038/sj.bjc.6603244
|View full text |Cite|
|
Sign up to set email alerts
|

Personality traits and cancer survival: a Danish cohort study

Abstract: We conducted a population-based prospective cohort study in Denmark to investigate associations between the personality traits and cancer survival. Between 1976Between and 1977Between , 1020 residents of the Copenhagen County completed a questionnaire eliciting information on personality traits and various health habits. The personality traits extraversion and neuroticism were measured using the short form of the Eysenck Personality Inventory. Follow-up in the Danish Cancer Registry for 1976 -2002 revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…Timid individuals avoid controversies and have a reconcilable condition of pathological wellness. Bleiker et al observed that tumour thickness in breast cancer patients was positively associated with ''type C'' personality, which is described as "unassertive, patient, cooperative, suppressive of negative emotions, and compliant with external authorities" (Nakaya et al, 2006). Persons with low levels of extraversion and high levels of neuroticism are thought to repress their emotion, which is considered to be one of the most important aspects of type C personality (Dean et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Timid individuals avoid controversies and have a reconcilable condition of pathological wellness. Bleiker et al observed that tumour thickness in breast cancer patients was positively associated with ''type C'' personality, which is described as "unassertive, patient, cooperative, suppressive of negative emotions, and compliant with external authorities" (Nakaya et al, 2006). Persons with low levels of extraversion and high levels of neuroticism are thought to repress their emotion, which is considered to be one of the most important aspects of type C personality (Dean et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, compared with healthy individuals, patients with laryngeal cancer are more prone to anxiety and emotional instability. Somewhat relatedly, one population-based prospective cohort study found a significant association between neuroticism and risk of death, particularly among women (28). Furthermore, a cross-sectional analysis from the Miyagi Cohort Study demonstrated that the personality traits of extraversion, neuroticism and psychoticism were significantly associated with attendance of gastric cancer screenings (29).…”
Section: Discussionmentioning
confidence: 99%
“…This is largely not because there are contrary findings but because almost no research has been conducted specifically pertaining to the relation between neuroticism and cancer and heart disease mortality. It appears that only Nakaya et al (2006) have found that higher neuroticism is associated with a greater chance of death from cancer, whereas Nakaya et al (2010) and Shipley et al (2007) have reported no relation. In regard to heart disease, it appears that only Shipley et al and Murberg et al (2001) have found that higher neuroticism is associated with a greater chance of death, but other researchers have not made a test of the potential link.…”
Section: Criterionmentioning
confidence: 97%